Promoting Marriage Readiness: Communication Strategies of Islamic Religious Counselors in Preventing Early Marriage - Mawaddatul Masthurah; Syukri Syamaun; Fitri Meliya Sari (Al-Hikmah Media Dakwah, Komunikasi, Sosial dan Kebudayaan, 2026)
Early marriage remains a significant social issue in Indonesia as it is closely related to educational, health, economic, cultural aspects, as well as individuals’ lack of readiness to build a household. This condition is also found in Blangkejeren District, thus requiring continuous preventive efforts through an educational approach. This study aims to analyze the roles, as well as the communication strategies and methods, of Islamic religious counselors in providing education on the prevention of early marriage at the Office of Religious Affairs (KUA) in Blangkejeren District. This research employs Everett M. Rogers’ Diffusion of Innovations theory using a descriptive qualitative method. Data were collected through observation, in-depth interviews, and documentation, with informants selected purposively. The findings reveal that Islamic religious counselors play roles as educators, motivators, counselors, mediators, and agents of social change in raising public awareness regarding the importance of delaying the age of marriage. The communication strategies applied include persuasive-religious approaches, direct engagement with adolescents and parents, participatory and collaborative approaches, as well as the utilization of social media and digital platforms. Meanwhile, the communication methods used consist of one-way communication, two-way communication, and verbal, written, and digital communication. The findings of this study highlight that the effectiveness of early marriage prevention education is determined by the counselors’ ability to adapt messages to the socio-cultural context of the community and to actively involve various stakeholders in the process.